2007
DOI: 10.1080/08858190701347838
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Motivations and Barriers to Patient Participation in Clinical Trials

Abstract: The findings suggest general support of CTs. Education programs are needed to raise awareness, reduce fears, and dispel myths about CT participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 0 publications
6
52
0
Order By: Relevance
“…24,25 Factors shown to influence participation in clinical trials were grouped into four themes: altruism, personal health benefit, monetary reimbursement, and convenience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Factors shown to influence participation in clinical trials were grouped into four themes: altruism, personal health benefit, monetary reimbursement, and convenience.…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with the literature. 24,25 The two highest scoring questions for motivating factors were AP technology could benefit others and improve the T1DM medical knowledge, with 88.9% and 77.7% of subjects reporting they strongly agree, respectively. The lowest scoring motivators of clinical trial participation were measures of convenience.…”
Section: Reliability Of Questionnairementioning
confidence: 99%
“…Previous studies have reported that 19–85% of the patients had positive attitudes about clinical trial participation [1,4,5,7,20]. In this study, 54.5–75.6% Chinese patients were willing to join a cancer clinical trial (table 3).…”
Section: Discussionmentioning
confidence: 61%
“…An important factor in carrying out successful clinical trials is the attitude of cancer patients towards such trials. A number of studies [1,2,3,4,5,6,7,8,9,10,11,12,13] have examined the attitude of patients toward enrolling in a cancer clinical trial. Although one study [1] showed that demographic factors do not influence patients’ willingness to participate, numerous other studies [6,7,8,9,10,11,12] revealed that patients’ attitudes toward clinical trials are related to their age, gender, stage of disease, education, religiousness and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…Public awareness, perceptions, and consequent attitudes toward clinical research may impact regulatory policies, guide research priorities, and shape growth in the sector; however, distrust, lack of awareness, and misconceptions of clinical research have been identified as key barriers to participation in clinical trials [61][62][63][64][65]. The PARTAKE initiative is based on the premise that an informed, participating public is invaluable for the following ethical, methodological, and operational reasons:…”
Section: Partakementioning
confidence: 99%